Key Performance Indicators for Food Supply Chain: A Bibliometric and Systematic Literature Review - Eleonora Bottani; Letizia Tebaldi; Giorgia Casella; Cristina Mora (Applied Sciences)
Key Performance Indicators (KPIs) are rates, percentages, or averages that convey information depending on their application field. In the Food Supply Chain (FSC), a comprehensive study is lacking. This paper fills the gap through a systematic literature review of 125 documents on FSC performance measurement. Bibliometric analysis shows a growing publication trend, with common keywords being KPIs, supply chain management, performance, and sustainability. Content analysis identifies nine FSC product types, with agricultural, dairy, and meat products being the most common categories. Similarly, three FSC areas (supply, production, distribution) are outlined, with production receiving the greatest attention. Finally, KPIs are classified into economic, environmental, and social sustainability categories, to highlight their relationships with the triple bottom line. A framework including the most common KPIs for each stage of the FSC is also proposed, together with the specific KPIs for the different product types.